2020
DOI: 10.11646/zootaxa.4749.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Checklist, Bibliography and Quantitative Data of the Arthropods of Hispaniola

Abstract: An updated and extensively revised checklist of the arthropods of Hispaniola (Dominican Republic and Haiti) is presented 11 years after the publication of the original in 2008. It integrates and quantifies all the terrestrial and surrounding marine arthropod species (plus those of Tardigrada and Onychophora), reported in the zoological literature for Hispaniola through the middle of 2019.        A total of 9,920 valid species (8,202 extant and 1,718 fossil) are listed, which represents an increase of 1,683 spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…The most heavily sampled and studied are Burmese amber (Cretaceous), Baltic amber (Eocene) and Dominican amber (Miocene). More than 3000 euarthropod species have been described from Baltic amber [ 29 ], nearly 1500 total species in Burmese amber [ 41 ] and nearly 1400 species from Dominican amber [ 42 ]. It is notable that previously described fossil tardigrade taxa are known from the less intensively sampled Canadian and New Jersey amber, with just over 100 and approximately 130 species reported, respectively [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most heavily sampled and studied are Burmese amber (Cretaceous), Baltic amber (Eocene) and Dominican amber (Miocene). More than 3000 euarthropod species have been described from Baltic amber [ 29 ], nearly 1500 total species in Burmese amber [ 41 ] and nearly 1400 species from Dominican amber [ 42 ]. It is notable that previously described fossil tardigrade taxa are known from the less intensively sampled Canadian and New Jersey amber, with just over 100 and approximately 130 species reported, respectively [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relatively young age of the Dominican amber, its euarthropod fauna is largely modern and most species are attributable to extant lineages among well-sampled groups. For example, although ants comprise between 25 and 35% of all Dominican amber inclusions and there are currently more than 80 described species from this deposit [ 47 ], only two of them are placed within extinct genera [ 42 ]. Some extant taxa were first described in Dominican amber prior to their discovery in extant neotropical communities, such as the ant genera Gracilidris and Leptomyrmex [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The seta of the tibia is basal and small, approximately 3 µm (Keifer, 1955). It is distinguished from P. oleivora (Ashmead, 1879), which has citrus plants as hosts and so far the only species of the genus reported in Hispaniola (Perez-Gelabert, 2020). Keifer (1955) reported that P. musae can be distinguished from P. oleivora, mainly by the elongate tibiae.…”
Section: Introductionmentioning
confidence: 99%
“…There exist no comprehensive Caribbean-centric revisions for any tortricid groups. Recent papers have begun to shed light on Caribbean tortricid diversity, but these have all been part of broader, Neotropical generic revisions (Razowski and Becker 2000b;Adamski and Brown 2001;Brown and Brown 2004;Phillips-Rodriguez and Powell 2007;Brown 2008;Razowski and Brown 2008;Brown 2009;Razowski and Becker 2010;Brown et al 2018), isolated taxonomic treatments (Matthews et al 2012(Matthews et al , 2019Brown et al 2018;Gilligan et al 2018;Austin et al 2019), or faunal inventories of the Lepidoptera in general (Núñez-Aguila & Barro-Cañamero 2012;Perez-Gelabert 2020). The present paper represents the first comprehensive taxonomic revision of a Caribbean tortricid tribe.…”
Section: Introductionmentioning
confidence: 99%